Time harmonic effects for rotor slot design considering deep bar squirrel cage induction motors - (:unkn) unknown (TRANSILVANIA UNIV PRESS-BRASOV, 2004)
Non sinusoidal distribution of MMF in induction motor introduce harmonics, which causes noise, overheating, low efficiency and vibration in the revolving parts of the motor. The distribution of 5(th) and 7(th) order harmonic currents in the rotor is highly effected by the slot shape of deep rotor bar. In this study optimum rotor slot shapes are analysed and optimisation process is implemented for high efficiency and low harmonic currents. The calculations are based on Kron's time equivalent circuit including the skin effect. The parameters and magnetic analysis of the motor is performed by Oersted simulation Program. The outputs are gathered in vector potential to be used In optimisation function with the aid of Fourier series expansion. In this paper, four slot shapes are given through analysed slots due to their tow harmonic currents and losses. The results are presented for 5(th) and 7(th) order harmonic currents. In addition efficiency versus rotor reactance graph is given. This paper represents an approach on the effect slot geometry in rotor harmonic currents to optimize harmonics and efficiency.
Keywords: harmonics; skin effect; rotor slot geometry